2019
DOI: 10.5603/fm.a2018.0096
|View full text |Cite
|
Sign up to set email alerts
|

Expression of matrix metalloproteinase-9 and tumour necrosis factor-alpha in the synovial cells of patients with meniscus tears

Abstract: Background: A meniscus tear is a serious trauma that develops during swinging motion of the fixed foot. Meniscus tears may also be accompanied by divergence of the lateral ligaments of the knee joint. Materials and methods: We enrolled 45 males and 35 females with meniscal tears in the present study. Patients with local joint pain, swelling, difficulty climbing stairs, patellar creeping, difficulties with daily living activities, local pain on palpation, and walking and running complaints, were included. We pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…To illustrate, both TNF-α and IL-1β are pro-in ammatory factors, which have been detected in synovial uid associated with knee trauma and OA [24]. TNF-α can act on articular cartilage through both autocrine and paracrine pathways to degrade the cartilage matrix of the knee joints.…”
Section: Discussionmentioning
confidence: 99%
“…To illustrate, both TNF-α and IL-1β are pro-in ammatory factors, which have been detected in synovial uid associated with knee trauma and OA [24]. TNF-α can act on articular cartilage through both autocrine and paracrine pathways to degrade the cartilage matrix of the knee joints.…”
Section: Discussionmentioning
confidence: 99%
“…They have studied degradive enzymes, metalloproteinases MMP-2 and MMP-3 activities using gelatin and casein zymography and revealed that active MMP-2 and total MMP-3 in meniscus were elevated. Atiç & Deveci (2019) have investigated the expression of matrix MMP-9 and TNFalpha in the synovial cells of patients with meniscus tears. They have found that fluid levels and inflammation in inflamed joints with meniscal tears were increased, and that disrupted the matrix of cartilage.…”
Section: Discussionmentioning
confidence: 99%